Optical backscattering by particles in Arctic seawater and relationships to particle mass concentration, size distribution, and bulk composition. (27th June 2016) - Reynolds, Rick A.; Stramski, Dariusz; Neukermans, Griet
Abstract: The magnitude and spectral shape of the optical backscattering coefficient of particles, b bp ( λ ), is being increasingly used to infer information about the particles present in seawater. Relationships between b bp and particle properties in the Arctic are poorly documented, and may differ from other oceanic regions which contribute the majority of data used to develop and parameterize optical models. We utilize recent field measurements from the Chukchi and Beaufort Seas to examine relationships between the spectral backscattering coefficient of particles in seawater and the mass concentration, bulk composition, and size distribution of the suspended particle assemblage. The particle backscattering coefficient spanned six orders of magnitude from the relatively clear waters of the Beaufort Sea to extremely turbid waters on the Mackenzie shelf. This coefficient was highly correlated with the mass concentration of particles, and to a lesser extent with other measures of concentration such as particulate organic carbon or chlorophyll a . Increased backscattering and high mass‐specific b bp ( λ ) was associated with mineral‐rich assemblages that tended to exhibit steeper size distributions, while reduced backscattering was associated with organic‐dominated assemblages having a greater contribution of large particles. Our results suggest that algorithms which employ composition‐specific relationships can lead to improved estimates of particle mass concentration from backscattering measurements. In contrast to theoretical models, however, we observe no clear relationship between the spectral slope of b bp ( λ ) and the slope of the particle size distribution in this environment.